The Rise of FinTech and the Journey Toward a Cashless Society: Investigating the Use of Mobile Payments by SMEs in Oman in the Context of Vision 2040 - Hisham Al Ghunaimi; Faozi A. Almaqtari; Ronald Wesonga; Ahmed Elmashtawy (Administrative Sciences)
This study investigates the factors that affect the adoption of mobile payment systems in Oman, focusing specifically on small and medium-sized enterprises (SMEs) within the expanding FinTech landscape. By utilizing secondary sources of data from the Central Bank of Oman and global FinTech reports, this research identifies essential enablers, such as security features and ease of use, which are propelled by developments in FinTech solutions. It also addresses the obstacles, such as high transaction fees and issues with authentication, that impede SMEs from embracing these technologies. Through an examination of worldwide FinTech adoption patterns, this research offers perspectives on Oman’s progress toward becoming a cashless society. This study employs sophisticated statistical techniques, including histograms and correlation analysis, to reveal significant trends in the rates of mobile payment adoption. The results emphasize the necessity for cooperative efforts among regulators, financial entities, and FinTech developers to minimize costs, strengthen digital infrastructure, and enhance user experiences. These findings are consistent with Oman’s Vision 2040, which aims to foster financial inclusion and propel the country’s shift toward a robust, digitally oriented economy powered by FinTech innovation.